Pemberdayaan Kelompok Katonik Mandiri Melalui Budidaya Rumput Laut Di Desa Komba-Komba Kecamatan Kabangka Kabupaten Muna - Agustina, Dewi Eva; Latang, Latang; Untung, Untung (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2025)
This study examines the empowerment of the Kelompok Katonik Mandiri in Komba-Komba Village, Kabangka District, Muna Regency. The problems in this study are 1) how to empower the Kelompok Katonik Mandiri Group in Komba-Komba Village, Kabangka District, Muna Regency and 2) what are the results of the empowerment of the Kelompok Katonik Mandiri in Komba-Komba Village, Kabangka District, Muna Regency. The purpose of this study is to describe: 1) the empowerment process starting from the awakening, understanding, harnessing and using stages and 2) the results of empowerment. This study uses a qualitative approach with a case study method. Data collection techniques are carried out by observation, interviews, and documentation. Informants consist of group leaders, group members, and community leaders. Data analysis techniques used in this study include: 1) data reduction, 2) data presentation, and 3) data verification and drawing conclusions. The techniques used to check the validity of the data in this study are source and technique triangulation. From the results of the research conducted, it was concluded that the community empowerment process was carried out through structured stages, starting from the awareness stage (awakening) which is becoming more independent, understanding (understanding) which is increasing ability, utilizing (harnessing) which is increasing group welfare, to using (using) which is using empowerment skills and abilities in themselves as part of everyday life. Intensification is carried out by utilizing existing resources optimally to increase production results. Diversification, namely producing seaweed chips products. Supporting factors in the empowerment of the Independent Katonik Group include the availability of facilities and infrastructure, provision of good materials, enthusiasm and motivation of members, support from the local government, and relevance to the location of residence. Inhibiting factors in the empowerment of the Independent Katonik Group include slow response, delays in providing necessary things, natural factors such as unfavorable weather. The results of this empowerment include economic aspects, increasing independence, environmental awareness, and welfare.